THE PERFORMANCE OF QUAIL STARTER-GROWER WHO WERE RATIONS ADDITIONAL CONTAINING GARLIC (Allium sativum) AND CARAWAY (Cuminum cyminum) - Florana, Bella; Dihansih, Elis; Handarini, Ristika (Jurnal Peternakan Nusantara, 2017)
Plants herbs widely used as a supplement in fodder to improve endurance and its productivity, including garlic and caraway. This study attempts to test the influence of the combination level of flour garlic and caraway performance against quail period of a starter up to the period grower. Study was conducted on  11 February  – 16 March 2017 in Assalam Slamet Quail Farm, Sukabumi.  This research was used 180  DOQ’s layer. Feed used were:  commercial feed BR-1 for stater and SP-2 for grower – layer, garlic flour and caraway flour. A complete randomized  design with four  treatments and three  replicates was used. Treatments consisted of  P0 = feed commercial (FC), P1 = PK + 2 % garlic flour (GF), P2 = PK + 2 % caraway flour (CF), P3 = PK + 1 % GF + 1 % CF. Research conducted in quail from 2 – 35 day. The variables were consumption, body weight gain, feed convertion ratio and mortality. Data were analyzed by a Duncan test. The results showed that  non-significant differences  on average body weight gain of stater  in the first week. The grower period showed that that non-significant differences on consumption and significant differences increased on average body weight gain in P2 treatment and decreased on feed convertion ratio in P1, P2 and P3. The conclusion showed the best research on supplement 2 % caraway flour to  grower quails. This conclusion was recommended to add 2 % caraway flour in quails feed.Keywords: performance of quails, feed additive, garlic, cumin.